PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK BERBASIS MODERASI BERAGAMA - Hasibuan, Faqih Hakim; Dira Puspita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a thematic learning model based on religious moderation with a valid, practical and efficient guidebook. Thematic learning focuses more on learning by doing. Religious moderation is an idea about how to understand and practice religious teachings so that they are always on a moderate path. This research was conducted at PTKIN North Sumatra, especially at UIN North Sumatra. The methodology used is research and development (R&D).